PROBLEM OF AIR POLLUTION IN CITIES (Центральноазиатский журнал образования и инноваций, 2024)
The article discusses the main environmental problems such as air pollution in cities, at the moment the existence of cities cannot be imagined without human anthropogenic impact. Humanity actively influences the state of the environment. The authors analyze the problem of urban pollution. The city is one of the types of social and spatial organization of the population, emerging and developing on the basis of the concentration of industrial, scientific, cultural, administrative and other functions.